(untitled) (Malay Literature, 2012)
This article is an exposition of the legendary character of Hang Tuah in the traditional Malay literary work titled Hang Tuah edited by Kassim Ahmad (1964), which is based on the manuscript Hikayat Hang Tuah from the collection of Dewan Bahasa and Pustaka. It traces the experiences of Hang Tuah, the main character, focusing on the development of his heroism. The concept of the construction of a hero is based on Joseph Campbell’s prototype model of the hero, whereby in his book The Hero with a Thousand Faces (first published 1949, third edition 2009), he summarizes every step of the hero’s journey into three stages: departure, initiation and return. The objective of the article is to examine Hang Tuah as a heroic figure using Campbell’s model as an archetype. The analysis will show the similarities in the treatment of the hero entity as an extraordinary person in Malay literature, while at the same time highlighting the most noticeable differences. The backbone of the construct is the contention that Hang Tuah’s heroism runs in tandem with the concept of king and kingdom in Malay tradition. Keywords: Hang Tuah, legendary warrior, Malay hero, hero’s journey